A compact microwave device for monitoring insect activity in grain samples. (November 2018) - Reimer, Alex; Wiebe, Kelsey; Rao, Jinwei; Yao, Bimu; Gui, Yongsheng; Jian, Fuji; Fields, Paul; Jayas, Digvir S.; Hu, Can-Ming
Abstract : We designed and fabricated a novel microwave device capable of detecting a single insect in grain samples. A test set-up was constructed by combining a planar active microwave resonator, a Peltier cell, and an insect cage. With the integration of a regenerative element, the active resonator had a quality factor as high as 21, 600 even when placed in grain, an electrically lossy medium. The high sensitivity of the device allowed the characterisation of the activity of single adult insects Tribolium castaneum or Cryptolestes ferrugineus at different temperatures, as well as the reliable detection of single adult insects in grain samples. Our approach demonstrated the non-contact sensing technique that could assist in decision making for integrated pest management programs to monitor insects in stored grain. Highlights: A high-Q microwave resonator sensor is presented that detects insect movement. Objects moving near the resonator change its resonant frequency. Detection is non-destructive and does not require contact. Insect activity can be monitored. Detection of insect activity in wheat grain samples was achieved for short ranges.